Positive effects of roflumilast on behavior, neuroinflammation, and white matter injury in mice with global cerebral ischemia. Issue 6 (26th July 2021) - Vilhena, Emanuella R.; Bonato, Jéssica M.; Schepers, Melissa; Kunieda, Juliana K.C.; Milani, Humberto; Vanmierlo, Tim; Prickaerts, Jos; de Oliveira, Rúbia M.W.
Abstract : Inhibition of phosphodiesterase 4 (PDE4) is a promising pharmacological strategy for the treatment of cerebral ischemic conditions. To increase the relevance and increase the translational value of preclinical studies, it is important to conduct experiments using different animal species and strains, different animal models, and to evaluate long-term functional outcomes after cerebral ischemia. In the present study, the effects of the selective PDE4 inhibitor roflumilast were evaluated in vivo and in vitro . Balb/c mice were subjected to bilateral common carotid artery occlusion (BCCAO) and tested during 21 days in multiple behavioral tasks to investigate the long-term effects of roflumilast on functional recovery. The effects of roflumilast were also investigated on hippocampal cell loss, white matter injury, and expression of neuroinflammatory markers. Roflumilast prevented cognitive and emotional deficits induced by BCCAO in mice. Roflumilast also prevented neurodegeneration and reduced the white matter damage in the brain of ischemic animals. Besides, roflumilast decreased Iba-1 (microglia marker) levels and increased Arginase-1 (Arg-1; microglia M2 phenotype marker) levels in the hippocampus of these mice. Likewise, roflumilast suppressed inducible nitric oxide synthase (microglia M1 phenotype marker) expression and increased Arg-1 levels in a primary mouse microglia culture. These findings support evidence that PDE4 inhibition by roflumilast might be beneficial in cerebral ischemic conditions. The neuroprotective effects of roflumilast appear to be mediated by a decrease in neuroinflammation.